Kemandirian Ekonomi Melalui Optimalisasi Peran Karang Taruna - Hanun, Nur Ravita; Fitriyah, Hadiah; Azara, Rima (Universitas Muhammadiyah Yogyakarta, 2020)
Karang Taruna (Youth Organization) becomes the hope for development resources in all aspects of the village. The village economic development needs to be directed towards the independence in order to be sustainable. Land resources that are productive but have not been utilized are potential to be the capital for the village economic independence development. The available land is used by Karang Taruna to be made as Vegetable and Fruit Gardens. The management of village’s Vegetable and Fruit Gardens has not been optimal yet. Thus, efforts in optimizing it need to be taken. The goal of community empowerment is to optimize the role of Karang Taruna of Keboan Anom Village and to develop the Vegetable and Fruit Gardens to achieve village economic independence. The community empowerment program is carried out in stages, namely socialization, training on processing food products, digital marketing workshops, and financial management. The results of community empowerment show that processed vegetables and fruit products having high economic value are produced as the source of income for Karang Taruna and as the additional income for Keboan Anom Village, the information technology-based marketing (digital marketing) models is well-understood, and the organizational financial management is good.